Analisis Derajat Ploidi dan Pengaruhnya Terhadap Variasi Ukuran Stomata dan Spora pada Adiantum raddianum - Perwati, Lilih Khotim (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2009)
Polyploidy is a common phenomenon in plants, especially on the species of ferns. The objectives of thisresearch are to find out the variation of the ploidy levels, to know the effects on the stomata index and size ofstomata and spore in Adiantum raddianum. The materials used to conduct this observation of chromosomes numberwere made from root tips or young leaf tips (croziers). The modified squash method was used in microscopicpreparation. The result of the observation showed that there was a variation in ploidy levels from 2n = 2x (diploid) to2n = 7x (septaploid). It appeared to be general trend that the higher level the ploidy causes the lower the indexstomata but the bigger the stomata and the spore size.